The identification of the new species Nitratireductor thuwali sp. nov. reveals the untapped diversity of hydrocarbon-degrading culturable bacteria from the arid mangrove sediments of the Red Sea - Marasco, Ramona; Michoud, Grégoire; Sefrji, Fatmah O.; Fusi, Marco; Antony, Chakkiath P.; Seferji, Kholoud A.; Barozzi, Alan; Merlino, Giuseppe; Daffonchio, Daniele (Frontiers in Microbiology, 2023)
The geological isolation, lack of freshwater inputs and specific internal water circulations make the Red Sea one of the most extreme—and unique—oceans on the planet. Its high temperature, salinity and oligotrophy, along with the consistent input of hydrocarbons due to its geology (e.g., deep-sea vents) and high oil tankers traffic, create the conditions that can drive and influence the assembly of unique marine (micro)biomes that evolved to cope with these multiple stressors. We hypothesise that mangrove sediments, as a model-specific marine environment of the Red Sea, act as microbial hotspots/reservoirs of such diversity not yet explored and described. To test our hypothesis, we combined oligotrophic media to mimic the Red Sea conditions and hydrocarbons as C-source (i.e., crude oil) with long incubation time to allow the cultivation of slow-growing environmentally (rare or uncommon) relevant bacteria. This approach reveals the vast diversity of taxonomically novel microbial hydrocarbon degraders within a collection of a few hundred isolates. Among these isolates, we characterized a novel species, Nitratireductor thuwali sp. nov., namely Nit1536T. It is an aerobic, heterotrophic, Gram-stain-negative bacterium with optimum growth at 37°C, 8 pH and 4% NaCl, whose genome and physiological analysis confirmed the adaptation to extreme and oligotrophic conditions of the Red Sea mangrove sediments. For instance, Nit1536T metabolizes different carbon substrates, including straight-chain alkanes and organic acids, and synthesises compatible solutes to survive in salty mangrove sediments. Our results showed that the Red Sea represent a source of yet unknown novel hydrocarbon degraders adapted to extreme marine conditions, and their discovery and characterization deserve further effort to unlock their biotechnological potential.